2018
DOI: 10.1136/esmoopen-2018-000414
|View full text |Cite
|
Sign up to set email alerts
|

Extra cost of brain metastases (BM) in patients with non-squamous non-small cell lung cancer (NSCLC): a French national hospital database analysis

Abstract: PurposeTo assess the incremental cost associated with the management of patients with primary non-squamous non-small cell lung cancer (NSCLC) with brain metastases at the time of diagnosis.MethodsData were extracted from the French Hospital medical information database (Programme de Médicalisation des Systèmes d’Information (PMSI)). Patients with non-squamous NSCLC were identified through a diagnosis of lung cancer and a prescription of bevacizumab or pemetrexed. All such patients hospitalised with lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…The analysis was limited to a set of six comorbidities of specific interest, namely hypertension, diabetes, renal failure, chronic obstructive pulmonary disease (COPD), pulmonary insufficiency and other chronic pulmonary disease. The presence of cerebral metastases at the index hospitalisation or any previous hospitalisation was documented as previously described [32].…”
Section: Data Extractionmentioning
confidence: 99%
“…The analysis was limited to a set of six comorbidities of specific interest, namely hypertension, diabetes, renal failure, chronic obstructive pulmonary disease (COPD), pulmonary insufficiency and other chronic pulmonary disease. The presence of cerebral metastases at the index hospitalisation or any previous hospitalisation was documented as previously described [32].…”
Section: Data Extractionmentioning
confidence: 99%
“…A specificity of the present modelling study was to include the impact on clinical and cost outcomes of the occurrence or progression of brain metastases using data from the ALEX study [13] to model the evolution of brain metastases over time and data from a recent hospital database analysis [26] to model costs. This is of particular relevance given that management of these metastases in NSCLC is a major unmet medical need [11], where alectinib can bring an important clinical benefit [12].…”
Section: Discussionmentioning
confidence: 99%
“…The modelling study indicates that use of alectinib in first-line Cost-effectiveness of alectinib in non-squamous NSCLC in France treatment can result in significant cost savings compared to crizotinib in the context of the French health care system. In addition, it is possible that the cost of brain metastases included in the model are underestimated, since, as pointed out in the source publication [26], only hospital costs and consultation by neuro-oncologist are considered and costs incurred in the community or in nursing homes, which may be considerable [31], are not taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the true figure will lie between the two, elective admissions in our review were limited only to elective surgical admissions with the remainder relating to unplanned emergency admissions. In France, a recent analysis of the cost of brain metastases in non‐small‐cell lung cancer demonstrated that the cost to health services of managing these patients was €533 per patient per month more than managing those with metastases elsewhere‐ a 22% difference (Girard et al, ).…”
Section: Discussionmentioning
confidence: 99%